Hello, topher0805!
You're reading the problem incorrectly.
. . means: .find , then substitute
Given that: .
Find for:
We have: .
- . - . .
Given that f(3) = -5, f '(3) = -2, g(3) = -2, and g'(3) = 3.
Find h'(3) for:
(a) h(x) = 2f(x) - 5g(x)
(b) h(x) = f(x)g(x)
(c) h(x) = f(x)/g(x)
(d) h(x) = g(x)/(2 + f(x))
As far as I know, the derivative of a constant is always 0. So when I plug in the values of f(x) and g(x) to find h(3) I always get a constant, and so the derivative of that must be zero, right?